Effect of 35% sodium ascorbate on calcium and phosphorus loss in dentin bleached by 35% hydrogen peroxide - Tunjung Nugraheni; Nuryono Nuryono; Siti Sunarintyas; Ema Mulyawati (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Post bleaching procedures often have free radicals trapped in dentin tubule and interprismatic enamel, leading to demineralization and denaturation. Sodium ascorbate is an antioxidant substance known to bind residual free radicals to stop demineralization and denaturation. The purpose of the study was to assess the calcium and phosphorus loss from the dentin surface following bleaching by 35% hydrogen peroxide and reversal by 35% sodium ascorbate andthe surface structure of the dentin. Six sound premolars were divided into their crown and root sections, with the crown subsequently being cut into four equal parts to obtain 24 samples. The calcium and phosphorus contents as well as the surface structure of the dentin were assessed using SEM-EDX. These were then divided into four groups, each containing six samples. Group A (control): the samples were bleached by 35% hydrogen peroxide, immersed in an artificial saliva, stored in an incubator at 37 °C for seven days. Group B: the samples were bleached by 35% hydrogen peroxide followed by the application of 35% sodium ascorbate for 5 minutes (once). Group C: the samples were bleached by 35% hydrogen peroxide followed by the applications of 35% sodium ascorbate (twice). Group D: the samples were bleached by 35% hydrogen peroxide followed by the applications of 35% sodium ascorbate (threetimes). The calcium and phosphorus contents as well as the surface structure of the dentin were re-assessed using SEM-EDX at the same locations. The results of one-way ANOVA indicated a difference in the calcium loss in the four treatment groups (p<0.05), but there was no difference in the phosphorus loss. An LSD test showed that there was a difference in the calcium loss between group A and groups C and D or between group B and groups C and D. The dentin tubules in group A were larger than group B, C and D. The frequency of 35% sodium ascorbate application had an effect on the calcium loss and the surface structure in the dentin bleached by 35% hydrogen peroxide.